Design of the Questionnaire: Fundamental Principles - Swati Patnaik1 , Shakti Swaroop2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The most critical aspect of investigative process, is the development of questions that correctly assesspublic perception, knowledge and behaviour. Precise random sampling and high answer rates are lost, if theinformation obtained is based on ambiguous or partial questions. Hence, in order to establish effective steps,a series of substantial questions are formulated and compiled in form of a Questionnaire.